Gross and applied anatomy pedagogical approaches in occupational therapy education: protocol for a scoping review - Emily S Ho; Anne Agur; Andrea Duncan; Erica Dove; Kelly Hennessy; Athena Kirou-Mauro; Lorna Aitkens (BMJ Open)
Introduction Historically, dissection is considered the ‘gold standard’ for teaching foundational anatomy to student occupational therapists. However, many programmes no longer have access to gross anatomy laboratory resources, as it is considered too costly. To address this limitation, applied anatomy instructors have developed innovative novel approaches to teach gross and applied anatomy to student occupational therapists, including live/surface anatomy, medical imaging, and more recently, computer-aided instruction. The types of different anatomy pedagogical approaches used and their impact on learning outcomes in occupational therapy education are unclear. The purpose of this scoping review is to map the types of musculoskeletal gross and applied anatomy pedagogical approaches used in occupational therapy curricula.Methods and analysis Using Arksey and O’Malley’s (2005) six-stage scoping review framework, approximately 304 different search combinations will be searched across five electronic library databases (ie, MEDLINE, Embase, CINAHL, AMED and ERIC) from their inception to December 2021, in addition to conducting consultation exercises with relevant stakeholders. After title/abstract and full-text screening, included articles will be charted, collated and summarised.Ethics and dissemination This study will not involve human or animal subjects. Therefore, research ethics approval is not required. The proposed scoping review will help the research, institutional and clinical rehabilitation communities to better understand the types of musculoskeletal gross and applied anatomy pedagogical approaches used to foster, build and promote musculoskeletal foundational knowledge in occupational therapy education. This could potentially inform the future physical medicine course curricula in occupational therapy programmes. The findings of this review will be disseminated to occupational therapy instructors, occupational therapists, researchers and organisations offering occupational therapy programmes (eg, Universities).